2021
DOI: 10.52562/jdle.v1i3.226
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Use Among Library and Information Science Students: A Case Study

Abstract: The purpose of this study is to identify the prevailing conditions of social media use among undergraduate students of Library and Information Science in a Nigerian University. Simple random sampling technique was used to select a sample of 180 full-time undergraduate students purposely. Descriptive statistics was used to analyze data collected through the administration of questionnaire. Research findings showed that a great number of students of Library and Information Science are addicted to social media fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…This corroborates earlier literature in Africa, which ascertained that males tend to display superior proficiency as Internet, ICT, or social media users in comparison to their female peers (McGregor et al, 2017;. Kasa et al (2021) highlighted a worrying trend of students' obsession with social networking, potentially affecting their academic, social, and spiritual well-being. Parents express concerns about their children's absorption in the virtual world, leading to detachment from reality.…”
Section: Literature Review and Hypotheses Developmentsupporting
confidence: 90%
“…This corroborates earlier literature in Africa, which ascertained that males tend to display superior proficiency as Internet, ICT, or social media users in comparison to their female peers (McGregor et al, 2017;. Kasa et al (2021) highlighted a worrying trend of students' obsession with social networking, potentially affecting their academic, social, and spiritual well-being. Parents express concerns about their children's absorption in the virtual world, leading to detachment from reality.…”
Section: Literature Review and Hypotheses Developmentsupporting
confidence: 90%
“…SM multitasking has been growing prevalent [2,17]. The heavy SM usage among undergraduates and its impact on their university performance was studied by Kasa et al [48], who found that a large proportion of students in a Nigerian University were addicted to social media for academic objectives. WhatsApp were the most addictive [40,48], and unexpectedly, those between the ages of 27 and 30 were the most obsessed.…”
Section: Sm Use and Academic Performancementioning
confidence: 99%
“…In this regard, the research indicated that SM should be employed for educational requirements, extending social networking platforms, creating new pages to improve learning activity, and monitoring must be conducted by teachers and parents on how the students use these sites. However, specialised awareness programs can be developed to highlight the dangers of social media addiction and to pave the path for students to balance their usage of social media platforms with academic activity [48].…”
Section: Sm Use and Academic Performancementioning
confidence: 99%